The Students’ Errors in Writing Analytical Exposition Text - Khoerunnisa, Khoerunnisa; Solihat, Dadang; Thamrin, Nani Ronsani (Verba: Journal of Applied Linguistics, 2023)
This research aims at analyzing mood structure and mood types in Kamala Harris’s Victory speech. Then, the researcher focuses on analyzing interpersonal function on M.A.K Halliday’s theory. They are Mood structure such as Mood element and Residue element, and then Mood Types such as Declarative, Imperative and Interrogative. Therefore, this research is to describe the Interpersonal function implemented in Kamala Harris’s Victory Speech and to find out the Mood types used in Kamala Harris’s Victory Speech. To analyze the data for this research, the researcher uses a qualitative method. The sources of data is video of Kamala Harris’s Victory Speech that has 11:31 minutes taken from website. Fortunaltely, the video has script that could be downloaded. Data analysis technique uses Miles and Huberman’s technique. According to the result, The researcher found that Interpersonal function was implemented by doing the analysis of Mood structure which consist of Mood and residue elements In Kamala Harris’s Victory Speech. The mood elements have Subjcets as the most dominant Mood elements that implemented in the speech with percentage of 56%. While for Residue elements, the most dominant one was Complement with percentage of 48%. The researcher found two types of mood which are used in Kamala Harris’s Victory speech, namely declarative mood (105 clauses, 95%) and Imperative (5 clauses, 5%). Declarative mood is the most dominant type of mood in Kamala Harris’s Victory speech that accurred 105 clauses with percentage 95% because speech deals with giving information to the audience.